Keanekaragaman Bakteri Tanah dari Teluk kodek Area, Pamenan Lombok Barat - Tri Ratna Sulistiyani (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
Indonesia is the center of the world's biodiversity with a unique biodiversity and priceless. To explore and get more information about biodiversity, strategic research was needed. The objective of this reseach was to explore the population diversity of soil microbes in Lombok Island. Bacterium isolates was identified by molecular 16S rDNA. Soil samples from 5 different sites in Lombok Island showed various bacteria population. The highest population 113 x 106 CFU/g soil was found in soil sample around Plumeria acuminata and the lowest 34 x 106CFU/g soil was found in soil sample around Tamarindus indica tree. Fourteen of isolates were identified using molecular identification with homology from 94 – 100%.